TRANSFORMATIONAL LEADERSHIP STYLE: HOW PRINCIPALS CAN HELP TO IMPROVE THE QUALITY OF LEARNING IN ELEMENTARY SCHOOL - Tika Ardiani; Sumarno Sumarno; Rasiman Rasiman (Program Studi PGSD Universitas Flores, 2025)
The improvement of the quality of SD Negeri 07 Purwoharjo cannot be separated from the principal's leadership in managing the school. This study aims to describe the implementation of the principal’s transformational leadership style in enhancing school quality, covering aspects of idealized influence, inspirational motivation, intellectual stimulation, and individual consideration. This research employed a qualitative method with data collected through observation, interviews, and documentation. Data analysis was conducted through the stages of data collection, condensation, presentation, and conclusion drawing. The validity of the data was ensured through source triangulation. The results of the study show: (1) Idealized influence is implemented through role modeling, transparency, fairness, care, communication of the vision and mission, and openness; (2) Inspirational motivation is realized through giving awards, fostering a familial atmosphere, listening to aspirations, and encouraging open communication and collaboration; (3) Intellectual stimulation is applied by promoting innovation, openness to new ideas, facilitating discussions, providing training, and supporting learning communities; (4) Individual consideration is carried out through personal attention and support, personal interactions, mentoring, and open communication with school members.